(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Graduate unemployment is a serious problem facing the Nigerian society for several years. This became a topical issue in the national discourse on how to come out of the problem. The quest to proffer solution to the problem of graduate unemployment gave way for the introduction of entrepreneurship education in tertiary institutions in Nigeria. Entrepreneurship education is an educational programme that creates awareness of entrepreneurship as a career option to enhance the understanding of the process involved in initiating and managing a new business enterprise. To achieve this at the entrepreneurship development centres, infrastructural facilities for skill acquisition at the centres should be adequate for effective entrepreneurial skills acquisition among undergraduates. This study determined the adequacy of infrastructural facilities for skill acquisition in entrepreneurship development centres in tertiary institutions in Enugu State. The study was a descriptive survey carried out with 39 management staff of entrepreneurship development centres and 98 entrepreneurship lecturers in tertiary institutions in Enugu State. One research question guided the study and two null hypotheses were tested at 0.05 level of significance. A validated structured questionnaire was used to collect data for the study. The reliability of the instrument was established using Cronbach Alpha which yielded the coefficient value of 0.73. Mean and standard deviation were used to analyze data to answer the research questions, z-test and ANOVA to test the null hypotheses. The findings of the study revealed among others that there are inadequate infrastructural facilities for skill acquisition in entrepreneurship development centres in tertiary institutions in Enugu State. It was recommended among others that the management of tertiary institutions in Enugu State should source for fund beyond government budgetary allocations through internal generated revenues and external grants to ensure adequate provision of infrastructural facilities for skill acquisition in Entrepreneurship Development Centres.